The Role of Family Harmony in Increasing Learning Motivation in Late Adolescents - Hermawan, Michael; Hendro Wibowo, Doddy (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The role of the family environment is crucial in supporting students' learning motivation. Internal factors that influence students' learning motivation involve various psychological aspects, such as self-confidence, self-esteem, as well as personal goals and aspirations. External factors also play a significant role in shaping learning motivation, including the social environment, peers, and teachers. The purpose of this study is to identify the relationship between family harmony and adolescent learning motivation. This study uses a quantitative method with a correlational design, employing the Family Harmony Scale (FHS) and the Motivated Strategies for Learning Questionnaire (MSLQ) as measurement tools. The results show that family harmony has a significant positive effect on adolescents' learning motivation. A harmonious family creates an emotionally supportive environment, enhancing adolescents' self-confidence and intrinsic motivation to achieve. The implication of this study highlights the importance of the family's role in shaping learning motivation, emphasizing the need for increased parental support and attention. Peran lingkungan keluarga menjadi sangat penting dalam mendukung motivasi belajar siswa. Faktor-faktor internal yang memengaruhi motivasi belajar siswa melibatkan berbagai aspek psikologis, seperti kepercayaan diri, harga diri, serta tujuan dan aspirasi pribadi. faktor eksternal juga memainkan peran yang tidak kalah penting dalam membentuk motivasi belajar. Lingkungan sosial, termasuk teman sebaya dan guru. Tujuan dari penelitian in adalah untuk mengidentifikasi hubungan antara keharmonisan keluarga dengan motivasi belajar remaja. Penelitian ini menggunakan metode kuantitatif dengan desain korelasional dengan alat ukur Family Harmony Scale (FHS) dan Motivated Strategies for Learning Questionnaire (MSLQ). Hasil Penelitian menunjukkan bahwa keharmonisan keluarga memiliki pengaruh positif yang signifikan terhadap motivasi belajar remaja. Keluarga yang harmonis menciptakan lingkungan emosional yang mendukung, meningkatkan rasa percaya diri dan motivasi intrinsik remaja untuk berprestasi. Implikasi penelitian ini yaitu pentingnya peran keluarga dalam membentuk motivasi belajar sehingga dukungan dan perhatian orang tua perlu diperkuat.